2022
DOI: 10.1177/00302228211051509
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Religiosity on Depression Trajectories After Widowhood

Abstract: This longitudinal study analyzed data from the 2006–2016 waves of the nationally representative Health and Retirement Study (HRS). Trajectories of depression among older adults ≥ 50 years ( N = 1254) were examined over time to explore patterns of depression among those entering widowhood and the potential impact of religiosity on depressive symptoms during various stages of widowhood. Ordinary least squares (OLS) regression analysis was used to examine the association between widowhood and depression and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Experiencing deep sadness is one of the normal responses felt when losing a partner. However, often deep sadness will cause a person to experience depression and an unstable mental state (Hawes, Tavares, Ronneberg, & Miller, 2022). To overcome this, it is necessary to increase resilience and the ability to recover from the grief experienced or what is also called resilience.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiencing deep sadness is one of the normal responses felt when losing a partner. However, often deep sadness will cause a person to experience depression and an unstable mental state (Hawes, Tavares, Ronneberg, & Miller, 2022). To overcome this, it is necessary to increase resilience and the ability to recover from the grief experienced or what is also called resilience.…”
Section: Resultsmentioning
confidence: 99%
“…Religiosity also has a close relationship with emotional well-being. It is said that someone with a high level of religiosity will not easily worry and experience depression (Hawes et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Living alone after the loss of a spouse can exacerbate this vulnerability due to reduced social support and increased loneliness (Cacioppo & Hawkley, 2006;Utz et al, 2014); and research has shown that living alone plays a mediating role in the relationship between widowhood and depression in older adults (Dean et al, 1992;Guo et al, 2021). Given the growing population of older adults living alone, understanding how to promote social connectedness and emotional well-being for widowers, especially those living alone, is crucial in addressing the negative health outcomes associated with widowhood, such as depression (Hawes et al, 2022;Jeon et al, 2017;Srivastava et al, 2021). Shielding factors that may aid in coping with loss have been identified through research (Recksiedler & Stawski, 2019;Stolzenberg & Waite, 2006), with religiosity being one such factor (Garcini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Hawes et al (2022) sheds light on the correlation between religiosity and experiences related to widowhood and depression, particularly among those adapting to a solitary lifestyle. Drawing on longitudinal data spanning from 2006 to 2016 from the Health and Retirement Study (HRS), their research focuses on individuals aged 50 and above to analyze depression trajectories in the context of widowhood.…”
Section: Introductionmentioning
confidence: 99%